THE EXPRESSION OF ANTIOXIDANT ENZYMES IN A MOUSE MODEL OF FETAL ALCOHOL SYNDROME - DREVER, Nathan (2012)
OBJECTIVE: Superoxide dismutase (SOD), glutathione peroxidase (GPx) and catalase (CAT) prevent cellular damage produced by free radicals. Our objective was to evaluate if prenatal alcohol exposure decreased the expression of antioxidant enzymes in the brain, liver or placenta of fetal mice. STUDY DESIGN: Timed, pregnant C57BL6/J mice were treated on gestational day 8 (E8) with intraperitoneal injection of alcohol (0.03 ml/g) or saline (control). Fetuses were harvested on E18. Fetal brain, liver and placenta were analyzed for mRNA expression of SOD, GPx and CAT by real-time PCR, with 18S RNA used as reference. RESULTS: SOD, GPx and CAT expression was lower in fetal brains exposed to alcohol with no differences detected in the liver or placenta between the two groups. CONCLUSION: Maternal alcohol consumption causes a decrease in SOD, GPx and CAT expression in the fetal brain. This may explain the long term neurologic findings in fetal alcohol syndrome.